Impact of Regular Low-Level Alcohol Consumption on Cognitive Interference and Response Inhibition: An fMRI Investigation in Young Adults - Hatchard, Taylor (Université d'Ottawa / University of Ottawa, 2017)
The purpose of the present dissertation was to shed light on the neurophysiological effect of regular consumption of low amounts of alcohol on two important aspects of executive functions, cognitive interference and response inhibition, using functional magnetic resonance imaging (fMRI) in a sample of young adults. Participants were recruited from the Ottawa Prenatal Prospective Study (OPPS), a longitudinal study that has collected data from participants from infancy to young adulthood, which permitted control of a number of potentially confounding drug and lifestyle variables. This allowed for investigation of the unique effect of alcohol use on executive functions. The dissertation itself is comprised of two original manuscripts: the first study compared low-level alcohol users to controls on performance of the Counting Stroop, a task of cognitive interference; and the second study compared users to controls on performance of the Go/No-Go, a task of response inhibition.Although the results of both studies found no performance differences between groups, low-level alcohol users had significantly more brain activation in several regions, including areas not typically associated with task processing, compared to irregular or non-drinker controls. This difference in neurophysiology may be reflective of compensatory strategies within the brain, whereby the recruitment of additional regions may be attempting to compensate for potential underlying deficits that occur with increasing cognitive demand. While further research is needed to validate this hypothesis, the present findings highlight the vulnerability of the developing brain.
Keywords: fMRI; Alcohol; Executive functions